Independent clinical research may alleviate disparities in cancer treatment - Matjaz Zwitter (Elsevier, 2016)
Disparities in cancer care are a reality of the modern world. Unfortunately, current clinical research is in the hands of for-profit pharmaceutical companies and of researchers from the developed world. Problems specific to cancer care in developing countries and among deprivileged populations are ignored. Independent clinical research can offer new valuable knowledge and identify affordable and cost-effective treatments. As such, research not depending on commercial sponsors should become one of the important avenues to alleviate the problem of cancer disparities.